Persepsi Kemudahan Penggunaan, Keamanan dan Kepercayaan sebagai Determinan Minat Penggunaan E-Wallet OVO - Maria Y Aryati Wahyuningrum; Nurul Khotimah; Rini Dwiastutiningsih; Anisah Anisah (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
Current digital wallet applications offer easy-to-use features, security levels, and trust by their users. The purpose of this study was to determine the effect of perceived ease of use, perceived security, and perceived trust on interest in using the OVO e-wallet application. The population in this study were people who were interested in using the OVO e-wallet application and had never used the OVO e-wallet application before in the Bekasi area. The sample taken in this study was 100 respondents. The sampling technique used was primary data where data collection was obtained by distributing online questionnaires via Google Form to the public. The test tool used was SPSS with analysis stages, namely validity test, reliability test, classical assumption test, multiple linear regression, t-test, f-test, dominant factor, and coefficient of determination (R2). The results of this study indicate that perceived ease of use, security, and trust have a partial effect on interest in use. Perception of ease of use, security, and trust have a simultaneous effect on interest in use of the OVO e-wallet application.